A brief guide to immunisation and the immunocompromised child or young person. (2nd January 2023) - Watson, Chloe; Davies, Barbara; Camara, Claire
Abstract : Vaccination of immunocompromised children is challenging both in regards to efficacy and safety. Chloe Watson, Barbara Davies and Claire Camara provide a brief overview Immunisation in children with a compromised immune system is not straightforward. Children with autoimmune disorders are especially at risk of vaccine-preventable diseases due to their underlying disease and the immunosuppressive treatment that is often required for a long period. This article explores some of the complexities that need to be considered when planning individual vaccination programmes.